Evaluation of a Tram Line with Ground-Level Energy Supply System in Energy Efficiency Perspective and Optimization Solution - Koyun, Ayhan; Yumurtaci, Recep (SAGE PUBLICATIONS INC, 2025)
Traction power consumption is an important part of energy consumption in railways. Many parameters, such as the geometric structure of the line, vehicle characteristics, and passenger density, affect the traction power consumption. Besides these parameters, the most important factor affecting the traction power consumption of a train is the speed profile of the train. Development of the speed profile has significant potential in energy efficiency. The objective of this study is to set an optimization model to minimize energy consumption and the size of the on-board energy storage device as much as possible, based on the appropriate train speed profile and recuperation of braking energy along the route, determined on a tram line with a ground-level energy supply system, and solving the optimization model by using a genetic algorithm (GA). In the study, a speed profile optimization is presented using GA. The objective function is to find the optimal maximum operation speed limit and speed profile that will reduce energy consumption and the on-board energy storage device size requirement within the specified running time based on operation expectations for each inter-station zone. In the mentioned speed profile optimization, constraints such as maximum and minimum running time for each inter-station zone, maximum operation speed limit for each inter-station zone, maximum acceleration and deceleration are taken into account. The simulation results show that energy savings for traction of up to 60% can be achieved compared with the existing system structure, with the usage of the recommended hybrid energy storage unit and optimized speed profile.
Keywords: optimization; resource conservation and recovery; energy harvesting; transportation energy; transportation network modeling and simulation; Engineering; Transportation